Pengaruh Sudut Kerja Pisau Potong Terhadap Unjuk Kerja Mesin Perajang Singkong - Syaifudin, Mohamad; Rubiono, Gatut; Qiram, Ikhwanul (Virtual of Mechanical Engineering Article, 2020)
Optimization of the cassava chopper machine can be done to minimize the consumption of electrical power required by the driving motor by changing the configuration of blade angle with rotation. This research was conducted experimentally by changing the angle of the knife on the chopper machine with an angle of 45, 60, and 90o. The rotation of the chopper shaft was varied by 150, 200, 250 rpm. Data was collected during the process by measuring the voltage and electric current on the motor using a digital avometer. In addition, video data and photos were collected using the camera. The results showed that the blade angle and rotation had an effect on the performance of the cassava chopper machine.